From Speaking to Writing for Transforming Everyday Arabic Dialogue into Simple Written Texts - Huda, Samsul; Muhammad Khoirul Umam; Rifqi Muzaki Husni; Fadhel Mubarak (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2024)
Mastering Arabic writing skills (Maharah Kitabah) remains a challenge for many learners, as traditional teaching methods often separate speaking and writing, making the transition between the two difficult. This study explores how structured interventions can bridge this gap by leveraging spoken Arabic as a foundation for writing. Conducted at Pesantren Darullughah Wadda’wah, this qualitative research involved 30 students who engaged in guided writing exercises transforming spoken dialogues into structured texts. Data collection methods included classroom observations, semi-structured interviews, and writing assessments, analyzed through thematic coding. The findings reveal that integrating dialogue-based exercises, sentence expansion techniques, and peer review significantly improves students’ writing fluency, grammatical accuracy, and confidence. Unlike conventional methods that emphasize rigid grammar instruction, this approach provides a more intuitive learning experience by helping students refine their speech into written form. While the study highlights the effectiveness of this strategy, it also acknowledges the need for long-term reinforcement to fully internalize written conventions. Future research should explore digital interventions and longitudinal studies to further enhance Arabic writing instruction.